2018
DOI: 10.1371/journal.pbio.2004877
|View full text |Cite
|
Sign up to set email alerts
|

Robust stochastic Turing patterns in the development of a one-dimensional cyanobacterial organism

Abstract: Under nitrogen deprivation, the one-dimensional cyanobacterial organism Anabaena sp. PCC 7120 develops patterns of single, nitrogen-fixing cells separated by nearly regular intervals of photosynthetic vegetative cells. We study a minimal, stochastic model of developmental patterns in Anabaena that includes a nondiffusing activator, two diffusing inhibitor morphogens, demographic fluctuations in the number of morphogen molecules, and filament growth. By tracking developing filaments, we provide experimental evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…The core regulatory circuit of heterocyst differentiation in Anabaena 7120 is summarized in Fig 7 . This coordination scenario involving multiple activating/inhibiting factors may help to refine the current models [ 51 , 52 ] for heterocyst differentiation and patterning.…”
Section: Discussionmentioning
confidence: 99%
“…The core regulatory circuit of heterocyst differentiation in Anabaena 7120 is summarized in Fig 7 . This coordination scenario involving multiple activating/inhibiting factors may help to refine the current models [ 51 , 52 ] for heterocyst differentiation and patterning.…”
Section: Discussionmentioning
confidence: 99%
“…The patS and hetN genes appeared in the E‐DIF and L‐DIF clusters, respectively. This is consistent with recent observations concerning the relative timing of their expression (Di Patti et al ., ), and the roles in early establishment (PatS) or maintenance (HetN) of the pattern (Yoon and Golden, ; Callahan and Buikema, ). Recently, it has been demonstrated that patS and hetN are not functionally equivalent when their promoter regions are switched, therefore suggesting their respective timing of expression is critical for proper function (Rivers et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…After the completion and acceptance of this work, an independent observation of stochastic Turing patterns in the cyanobacteria colonies of Anabaena sp. was reported (31).…”
Section: Methodsmentioning
confidence: 96%